2018
DOI: 10.12693/aphyspola.133.1174
|View full text |Cite
|
Sign up to set email alerts
|

A Diffusion Model for the Fe2B Layers Formed on a Ductile Cast Iron

Abstract: In this work, a diffusion model was applied to estimate the boron diffusion coefficients in the Fe2B layers on the ASTM A-536 ductile iron in the temperature range 1173-1273 K by the powder-pack boriding. The mass balance equation at the (Fe2B/substrate) interface was formulated considering the effect of boride incubation times. As a result, the value of activation energy for boron diffusion in the ductile iron was estimated and compared with the literature. To verify the validity of the present model, the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The three time-dependent unknowns a(t), b(t) and u(t) are subjected to the boundary conditions given by Eqns. 2and (3). Eq.…”
Section: The Integral Diffusion Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The three time-dependent unknowns a(t), b(t) and u(t) are subjected to the boundary conditions given by Eqns. 2and (3). Eq.…”
Section: The Integral Diffusion Modelmentioning
confidence: 99%
“…(13) was obtained from the graph displayed in Figure 6 by a linear fitting of data with a coefficient of determination close to unity. In Table 3 are gathered the values of activation energies for boron diffusion in some pack-borided cast irons [3,6,11,25] with the value of activation energy for boron diffusion in EN-GJL-250 lamellar gray cast iron estimated in this work. The found value of activation energy for boron diffusion (=163.86 kJ mol -1 ) is required to overcome the energetic barrier allowing the diffusion of boron atoms inside the material substrate.…”
Section: Estimation Of the Value Of Activation For Boron Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent work, published by Keddam et al [19], a kinetic model has been proposed to study the growth kinetics of FeB and Fe 2 B layers on AISI D2 steel where the effect of diffusion annealing process was taken into account. Keddam et al [20] suggested another approach to investigate the boronizing kinetics of a cast iron by using a different mathematical model. Some of these models are developed without considering the presence of incubation times of borided layer.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the modeling of boriding kinetics is crucial for optimizing the desired boride layer thickness that matches the practical utilization of borided steels at industrial scale. To reach this objective, several studies were devoted in the literature for modeling the boriding kinetics of ferrous alloys: (Armco iron [3][4][5][6], steels [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and cast irons [25][26][27][28]) by using different approaches.…”
Section: Introductionmentioning
confidence: 99%